IMPLEMENTASI WATERMARKING PADA SUARA DIGITAL DENGAN METODE DATA ECHO HIDING - Piarsa, I Nyoman; Ady Dharmadi, I Made (Jurnal Teknologi Elektro; JURNAL TEKNOLOGI ELEKTRO, 2012)
Digitally recorded especially for audio give us many advantage in data processing or manipulation. However digitally recorded also avoid violation of data royalty like illegally duplicating, cropping half or all of data and disttributing without permission from owner of audio data. Based on that problem, there are need one proving system for digital media, and watermarking technique can be applied for that purpose. The model design conducted with sets of system model method and watermarking method will apllied is Echo Hiding Technique.Analysis is by testing emmbedding and extracting watermark testing, capacity embedding testing and robustnes of watermark attack test. Analysys test for watermarking technique showing degradation of perceptual quality of audio file after watermarked. In extraction test , Echo Hiding technique, watermark recovery rate depend on initial amplitude. There is no change in size of audio file before and after watermarking process. In robustness test result that Echo hiding Technique have highly robustness.